Dispersion modelling of potentially toxic elements and particulate matter concentrations from the stack of Shahid Rajaei power plant using the AERMOD method - Ali Godarzvand chegini; Naser Ebadati; Behnoush Khoshmanesh Zadeh (Anthropogenic Pollution)
This study was conducted with the aim of evaluating the dispersion of suspended particles and potentially toxic elements in the air and soil around Shahid Rajaei Thermal Power Plant. For this purpose, soil sampling was carried out in a regular network with a radius of 10 km to measure the concentration of potentially toxic elements, and separately, the distribution model of particles and potentially toxic elements released from the power plant chimney was determined using AERMOD software up to a distance of 25 km. Results showed that the concentration of potentially toxic elements in the soil around the power plant has a direct relationship with the particles coming out of the power plant chimney and their deposition in the soil, and the trend of soil pollution up to a distance of 8 to 10 km from the power plant shows the highest concentration of the studied elements, and with increasing distance from the power plant, Pollution levels are reduced. In the affected areas, the concentrations of vanadium, nickel, zinc, and copper exceeded the standard with values ​​of 237, 88,210 and 112 ppm, respectively, and the four elements cobalt, chromium, molybdenum, and lead with values 21, 115, 4.7 and 42 ppm showed lower levels of pollution. which are also related to the type of fuel consumed by the power plant. Modeling of particle dispersion in the air by AERMOD method with the trend of dispersion and concentration of the above elements is consistent with the analysis of soil pollution.